LECTURER’S WRITTEN CORRECTION IN WRITING CLASS A Case Study at Universitas Veteran Bangun Nusantara Sukoharjo in Academic Year 2013/2014 - Dayat Dayat (IKIP PGRI Pontianak, 2014)
Written correction is the important part of FL writing instruction. The aims of this research are to find: (1) how the lecturer gives written correction to student’s writing; (2) how the students respond to the lecturer’s written correction (LWC); and (3) how far LWC affects the students’ improvement in writing accuracy. This study is a case study where the participants are one writing lecturer and eight students at a private University in Central Java. Interviews, direct observation and documentary analysis were used in this study. The findings show that the lecturer used direct/indirect correction; metalinguistics (error code); focused/unfocused; and reformulation by underlining, crossing, and striking through to the incorrect forms. The correction was provided after the students submitted their final draft to the lecturer. All students preferred direct correction to other types and they made use of the correction for their learning through revising it. Finally, LWC affected the students’ improvement on writing accuracy. Keyword: Written Correction, Types of Written Correction, The Students’ Responses, Case Study.